Odpowiedzi

  • uire
  • Rozwiązujący
2010-04-13T22:13:40+02:00
A)
x²-4-x²+4x-4=-y
-y=4x-8
y=-4x+8
b)
y²+2y+1 - 4x²-2x = y²-4x²+3x
2y - 5x + 1 = 0
2y = 5x-1 |÷2
y = 5/2x - 1/2
Najlepsza Odpowiedź!
2010-04-13T22:24:05+02:00
A) (x-2)(x+2)-(x-2)²=-y
(x-2)(x+2)-(x-2)(x+2)=y
2x-4+2x-4=y
4x-8=y
y=-4x+8

(y+1)²-x(4x+2)=(y+2x)(y-2x)+3x i ma wyjsc y=5/2x - ½
y+2y+1-4x2-2x= y-4x2+3x
(y i 4x2 się skrócą po obu stronach)
później:
2y+1- 2x=3x
2y-2x-3x=-1
2y-5x=-1
2y=-1+5x /2
y=-1/2+5x/2


Prosze :))

1 5 1
2010-04-13T22:29:42+02:00
A) (x-2)(x+2)- (x-2)²=-y
x²+2x-2x-4-x²+2x-4=-y
4x-8=-y
y=-4x+8

b)(y-1)²-x(4x+2)=(y+2x)(y-2x)+3x
y²+2y+1-4x²-2x=y²-2xy+2xy-4x²+3x
y²+2y-y²=-4x²+3x-1+4x²=2x
2y=5x-1 //:(2)
y=2,5x-0,5